Exploring the expected lifestyle among older adults in Klang Valley, Malaysia - Yong, Jun Yin; Toh, Guat Guan; Lim, Chia Yien; Chong, Shyue Chuan (Journal of Social Economics Research, 2024)
This paper examines the relationship between financial status, quality of life, happiness, and expected retirement lifestyle among older adults, particularly those who are over 60 years old and residing in the Klang Valley region of Malaysia. We developed the research framework by integrating social support theory and quality of life theory. The data were obtained by utilising non-probability sampling, quota sampling techniques and a Google Form-based face-to-face interview with 250 older adults in Klang Valley (Kuala Lumpur and Selangor), Malaysia, conducted between May and July 2023. The study’s findings revealed a strong positive correlation between the financial situation of older adults’ and their level of happiness, as well as between their quality of life and financial status. Additionally, this study discovered that the quality of life of adults acts as a significant mediator between expected retirement lifestyle, financial status, and happiness. A key factor influencing the quality of life and expected lifestyle of the retired population is the financial status and happiness of older adults. Meanwhile, older adults’ quality of life serves as a significant mediator between their financial status and their level of happiness with their expected lifestyle. The paper provides practical implications to various stakeholders, including government, companies, businesses, and communities, in establishing policies or providing suitable products and services to accommodate the needs and well-being of the older adults.